Optimum compressive pressure and thermal treatment for effective mahang wood densification - Wong, Thye Seang (2013)
Wood densification can be done by mechanical means involving heat and moisture. However, mechanically densified wood is dimensionally unstable. Compressive deformation could be fix by applying pressure above the elastic limit but lower than the maximum compression load. Therefore, compressive pressure becomes an important parameter and no stopper’s bars or molds are used to limit the compression. Determination of the optimum compressive pressure for densification provides a new innovative way in densifying wood without experiencing compressive failure. Densified wood was successfully produced from ten-year-old mahang wood (Macarangga gigantea) having initial density of 274±26 kg/m3. Transverse compression strength in radial direction of steamed and unsteamed mahang wood was determined prior to calculating the required compression pressure. The steaming duration was 15, 30 and 45 min. After analysis using the stress-strain curve, the compressive strength was converted into compressive pressure. The After pre-steamed in a closed vessel at 130 °C for either 15, 30 or 45 min, all the pre-steamed mahang woods were densified by compressing the wood at a specific pressure that was pre-determined. After cooling and conditioning at dry condition (under silica gel) for two weeks, the densified wood was tested for the dimensional stability and strength properties. The wood was successfully compressed at 75-78% compression ratio without any visual physical defects and springback. Compressive pressures between 0.91 kgf/mm2 to 2.04 kgf/mm2 were using for compressing steamed mahang wood (15, 30 and 45 min steaming). The densified mahang wood was tested for bending strength, shear modulus and dimensional stability. The dimensional stability of densified mahang wood was evaluated after conditioning at 45%, 65%, 85% and 100% RH at 25 °C. The maximum thickness swelling was 43.49% after being conditioning in 100% RH at 25 °C until constant reading for 29 days. However, the thickness swelling was less than 3% after conditioning at 45% and 65% RH. Therefore, all densified wood specimens for bending strength and shear modulus were condition at 65% RH. The results showed the bending strength of densified mahang was as high as 137.37 MPa, Modulus of Elasticity (MOE) was 16.80 GPa and shear modulus was 1.13 GPa. The result shows that the approach used in this study is effective for densification of low density (<300 kg/m3) wood into about 300% of the original density. Although the thickness recovery is still high, higher compressive pressure improved dimensional stability. Thirty minutes steaming pre-treatment at 130 °C provides an optimum condition for densification of mahang wood producing densified mahang of high strength and dimensional stability.